EFL Students' Perception on Webtoon: Reading Activity - Beatrix Angelica; Caroline Victorine Katemba (Institut Agama Islam Negeri Madura, 2023)
Nowadays, the digital era offers many creative platforms to help EFL students gain more English knowledge and comprehend all English skills, particularly reading. Leisure reading, like Webtoon, is the most popular platform for practicing reading among millennials. Webtoon is a digital comic with a colorful design and various stories for readers to enjoy. Nowadays, the digital era provides many creative platforms to assist EFL students in gaining more knowledge in English to comprehend all English skills, especially in reading. The most platform for practicing reading millennials use is leisure reading, such as Webtoon. Webtoon is a digital comic with a colorful design and has many kinds of stories that eager readers to read. Therefore, this research seeks to determine EFL students' perceptions of both state and private universities about Webtoon on reading activity. This study was a quantitative research design. The data were gathered through questionnaires distributed to the students. The result revealed a positive perception of the students toward using Webtoon as reading reactivity.